2021
DOI: 10.1016/j.ijrobp.2021.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prognostic Value of High-Sensitivity Cardiac Troponin T for Early Prediction of Chemoradiation Therapy-Induced Cardiotoxicity in Patients with Non-Small Cell Lung Cancer: A Secondary Analysis of a Prospective Randomized Trial

Abstract: Research data are stored in an institutional repository and will be shared upon request to the corresponding author.Acknowledgments-The high-sensitivity cardiac troponin (hs-cTnT) reagents were provided by Roche Diagnostics, Indianapolis, Indiana, as part of a research agreement. The funding agencies and Roche Diagnostics played no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In a study of 225 patients with non‐small cell lung cancer (NSCLC), elevated hs‐cTnT levels during concurrent dual chemotherapy with platinum and paclitaxel and chest radiotherapy were dependent on radiation heart dose. Hs‐cTnT levels were associated with CTRCD and mortality, and routine monitoring of hs‐cTnT could identify patients at high risk of CTRCD due to radiotherapy at an early stage 29 . The study by Finke et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 225 patients with non‐small cell lung cancer (NSCLC), elevated hs‐cTnT levels during concurrent dual chemotherapy with platinum and paclitaxel and chest radiotherapy were dependent on radiation heart dose. Hs‐cTnT levels were associated with CTRCD and mortality, and routine monitoring of hs‐cTnT could identify patients at high risk of CTRCD due to radiotherapy at an early stage 29 . The study by Finke et al .…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [74], in their study, stated that elevation of hsTnT during chemoradiation therapy was radiation heart dose-dependent and was associated with cardiac adverse events and mortality. They…”
Section: Role Of Biomarkersmentioning
confidence: 99%
“…Secondary analyses of the data are ongoing to understand the role of various factors, including inter-and intra-fractional variations in anatomy, the simplistic assumption about proton RBE, immature technology (PSPT instead of IMPT), and evolving treatment planning techniques. [55][56][57][58][59][60][61][62][63][64][65] • For esophageal cancers, retrospective studies suggested reduced toxicity rates and promising disease control rates with proton therapy. Based on these findings, a multi-institutional randomized trial of protons versus photons for esophageal cancer was conducted.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Secondary analyses of the data are ongoing to understand the role of various factors, including inter‐ and intra‐fractional variations in anatomy, the simplistic assumption about proton RBE, immature technology (PSPT instead of IMPT), and evolving treatment planning techniques. [ 55–65 ] At the same time a multi‐institutional randomized phase III study “Comparing Photon Therapy To Proton Therapy To Treat Patients With Lung Cancer” (NCT01993810) is underway through NRG and is nearing completion. Another phase II randomized trial “Image‐Guided, Intensity‐Modulated Photon or Proton Beam Radiation Therapy in Treating Patients with Stage II‐IIIB Non‐small Cell Lung Cancer” (NCT01629498) is also being conducted. For esophageal cancers, retrospective studies suggested reduced toxicity rates and promising disease control rates with proton therapy.…”
Section: Clinical Outcomesmentioning
confidence: 99%